THE ITERATION METHOD OF THE FIRST BOUNDARY-VALUE PROBLEM SOLUTION WITH NONLINEAR RIGHT-HAND SIDE - Laguta, V. V. (Science and Transport Progress, 2007)
The numerical method of the decision of the first boundery problem with the nonlinear ordinary differential equation of the second order is offered. The initial problem is reduced to the decision of the two integrated equations with use Green's function. The system is solved Picard's method.